The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.12688/wellcomeopenres.16020.2
|View full text |Cite
|
Sign up to set email alerts
|

The Avon Longitudinal Study of Parents and Children - A resource for COVID-19 research: Questionnaire data capture April-May 2020

Abstract: The Avon Longitudinal Study of Parents and Children (ALSPAC) is a prospective population-based cohort study which recruited pregnant women in 1990-1992. The resource provides an informative and efficient setting for collecting data on the current coronavirus 2019 (COVID-19) pandemic. In early March 2020, a questionnaire was developed in collaboration with other longitudinal population studies to ensure cross-cohort comparability. It targeted retrospective and current COVID-19 infection information (exposure as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(58 citation statements)
references
References 9 publications
1
56
1
Order By: Relevance
“…We were able to assess some key sociodemographic factors predicting questionnaire completion, which is important for assessing and quantifying the extent of possible selection and collider bias, which may bias both our prevalence estimates and associations between variables 20 . As reported both here and previously 10 , 11 , questionnaire response is socially patterned, with older, female, and higher-socioeconomic position participants more likely to respond. Additionally, in this questionnaire participants who previously reported that they had COVID-19 were more likely to respond.…”
Section: Strengths and Limitations Of The Datasupporting
confidence: 83%
See 2 more Smart Citations
“…We were able to assess some key sociodemographic factors predicting questionnaire completion, which is important for assessing and quantifying the extent of possible selection and collider bias, which may bias both our prevalence estimates and associations between variables 20 . As reported both here and previously 10 , 11 , questionnaire response is socially patterned, with older, female, and higher-socioeconomic position participants more likely to respond. Additionally, in this questionnaire participants who previously reported that they had COVID-19 were more likely to respond.…”
Section: Strengths and Limitations Of The Datasupporting
confidence: 83%
“…As with the previous COVID-19 questionnaires 10,11 , women were more likely to return the questionnaire than men. Individuals who had previously self-reported that they had had COVID-19 (from either a positive test, doctor suspicions or own suspicions) were more likely to complete this third questionnaire.…”
Section: Key Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…Additionally, although not explored directly in this data note, previous ALSPAC data notes [8][9][10][11] and other research 24 has established that invitation and response to ALSPAC's COVID-19 data collection is non-random (e.g., with participants who are older, female, white and from higher socioeconomic backgrounds -among other factors -more likely to be invited and respond). Analyses using this data may therefore potentially be subject to selection bias, which may bias both prevalence estimates in this population and associations between variables [25][26][27] .…”
Section: Whole Alspac Cohortmentioning
confidence: 99%
“…Pre-pandemic high-risk drinking, smoking (no/yes), and e-cigarette use (no/yes; young people only), were assessed at different time points (2012)(2013)(2014)(2015)(2016)(2017). Early pandemic risk/protective behaviours (self-isolating, social contact) were assessed in the first COVID-19 online questionnaire (09.04.20-15.05.20) (Northstone et al, 2020a).…”
Section: Risk Behavioursmentioning
confidence: 99%